Diagnosis and treatment of diabetic polineuropathy (Przewodnik Lekarza/Guide for GPs, 2007)
Diabetic neuropathy is one of the most common microvascular complications of diabetes. Peripheral polineuropathy is the most frequent type of this complication. Pain connected with advanced grade of peripheral polineuropathy is a very important clinical problem. It deteriorates patient’s quality of life and may lead to depression and suicidal attempts in extreme cases. However diagnosis of diabetic polineuropathy is straight foreward effective treatment remains a problem.